2015
DOI: 10.1002/prca.201500030
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac extracellular matrix proteomics: Challenges, techniques, and clinical implications

Abstract: Extracellular matrix (ECM) has emerged as a dynamic tissue component, providing not only structural support, but also functionally participating in a wide range of signaling events during development, injury and disease remodeling. Investigation of dynamic changes in cardiac ECM proteome is challenging due to the relative insolubility of ECM proteins, which results from their macromolecular nature, extensive post-translational modifications and tendency to form protein complexes. Finally, the relative abundanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 63 publications
0
38
0
3
Order By: Relevance
“…However, studies have shown successful decellularization using SDS without damaging the components of the ECM (Garrigues et al, ; He & Callanan, ; Oberwallner et al, ; Sullivan et al, ). Furthermore, a thorough proteomic study of the ECM components and the cellular secretome would act as validation for the PCR results and would give a better understanding of which proteins lead to the improved adhesive properties (Chang, Dalgliesh, Lopez, et al, ; Hathout, ). Further analysis on how the ECM was incorporated into the electrospun fibers is required.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown successful decellularization using SDS without damaging the components of the ECM (Garrigues et al, ; He & Callanan, ; Oberwallner et al, ; Sullivan et al, ). Furthermore, a thorough proteomic study of the ECM components and the cellular secretome would act as validation for the PCR results and would give a better understanding of which proteins lead to the improved adhesive properties (Chang, Dalgliesh, Lopez, et al, ; Hathout, ). Further analysis on how the ECM was incorporated into the electrospun fibers is required.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanical micro-environment likely accounts for only a portion of the short-range maturational cues. The cardiac extracellular matrix (ECM) is a complex assembly of glycosaminoglycans, glycoproteins, and adhesive proteoglycans that have both signaling and mechanical functions [54]. Cardiomyocytes grown on decellularized heart ECM showed greater maturation as measured by protein expression than cells grown on mechanically similar liver ECM [55].…”
Section: Discussionmentioning
confidence: 99%
“…Normalizing protein content to MC numbers and/or types should maximize the confidence that future proteomic analysis in cardiac growth is representative of variable MCs changes in size. LP-FACS purified MCs also offer a new entry point for cell-specific analysis into relationship between cellular organization and function, as well as variations in normal cardiac tissues 50 at the level of individual cells.…”
Section: Discussionmentioning
confidence: 99%